2022
DOI: 10.1101/2022.04.20.488069
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial effects on fertility and longevity in Tigriopus californicus contradict predictions of the mother’s curse hypothesis

Abstract: SUMMARYStrict maternal inheritance of mitochondria favors the evolutionary accumulation of sex-biased fitness effects, as mitochondrial evolution occurs exclusively in female lineages. The “mother’s curse” hypothesis proposes that male-harming mutations should accumulate in mitochondrial genomes when they have neutral or beneficial effects on female fitness. Rigorous empirical tests have largely focused on Drosophila, where support for the predictions of mother’s curse has been mixed. We investigated the impac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 99 publications
0
12
0
Order By: Relevance
“…For instance, Li et al (2022) found that females had longer lifespans than males in F1 inter-population hybrids, and Foley et al (2013) showed that differences in nuclear allele frequencies between reciprocal F 2 hybrids (i.e., between alternate mitochondrial genotypes) were sex-dependent, particularly for chromosome 10. However, observed sex-specific effects in hybrid T. californicus are not consistently aligned with the expectations of the ‘mother’s curse’ hypothesis (e.g., Watson et al, 2022), and although previous results have indicated that variation in developmental rate is generally highly dependent on mitonuclear compatibility in T. californicus hybrids (Healy & Burton, 2020; Han & Barreto, 2021), variation in this trait between the sexes was virtually absent at any stage of development in the current study (consistent with the less detailed results of Burton [1990]). Similarly, variation in mitonuclear effects on developmental time between females and males is generally modest or absent in Drosophila sp.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…For instance, Li et al (2022) found that females had longer lifespans than males in F1 inter-population hybrids, and Foley et al (2013) showed that differences in nuclear allele frequencies between reciprocal F 2 hybrids (i.e., between alternate mitochondrial genotypes) were sex-dependent, particularly for chromosome 10. However, observed sex-specific effects in hybrid T. californicus are not consistently aligned with the expectations of the ‘mother’s curse’ hypothesis (e.g., Watson et al, 2022), and although previous results have indicated that variation in developmental rate is generally highly dependent on mitonuclear compatibility in T. californicus hybrids (Healy & Burton, 2020; Han & Barreto, 2021), variation in this trait between the sexes was virtually absent at any stage of development in the current study (consistent with the less detailed results of Burton [1990]). Similarly, variation in mitonuclear effects on developmental time between females and males is generally modest or absent in Drosophila sp.…”
Section: Discussionmentioning
confidence: 67%
“…Alternatively, following from the expectations of a ‘mother’s curse’, decreased reliance on complex I respiration in males could partially negate the possibility of strong effects of mitonuclear incompatibilities on complex I function in this sex. In either case, variation in the proportional contributions of complex I and II respiration between females and males may contribute to the sex-specific effects of incompatibilities on viability, lifespan or longevity reported elsewhere (Willett & Burton, 2001; Li et al, 2022; Watson et al, 2022).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations